Assessment of Nigella Sativa Induced Adverse Drug Reactions - SM, Jaffar; KB, Chandrasekhar; RY, Padmanabha; S, Bushra (Indian Journal of Pharmacy Practice)
Objective: Monitoring of Adverse Drug Reactions (ADRs) with intake of Nigella sativa was carried out in a primary care Ayurvedic hospital. Patients were counseled and information regarding their medical and medication history was taken. Methodology: The people who were using Nigella sativa as drug were followed for a period of 6 months prospectively. Naranjo's algorithm, WHO probability scale, Modified Hartwig and Seigel scale and Modified Shumock and Thornton scales were employed to assess the Causality, Severity and Preventability of the ADRs. Results: At the end of the study 22 ADRs were observed with the usage of Nigella sativa for the maintenance of normal health. Among the ADRs 45.45% were found Possible and 54.54% were found Probable (Naranjo's algorithm). Conclusion: In assessment of severity level all the ADRs (100%) were mild and definitely preventable. Even with these ADRs, the medication was not discontinued but dose adjustment was done in all the cases.
Keywords: Seeds; Nigella sativa; Adverse Drug Reactions; Alternate Medicine